Within‐Family Relations in Objective Sleep Duration, Quality, and Schedule. Issue 6 (10th November 2016) - Kouros, Chrystyna D.; El‐Sheikh, Mona
Abstract : The current study examined within‐family relations between mothers', fathers', and children's objectively assessed sleep. Participants were 163 children ( M age = 10.45 years; SD = 0.62) and their parents. For 7 nights, families wore actigraphs to assess sleep duration (minutes), quality (efficiency, long wake episode, total wake minutes), and schedule (wake time). A sleep log assessed bedtime. Multilevel models indicated that children's sleep minutes, sleep efficiency, wake minutes, and wake time were associated with fluctuations in their mothers', but not fathers', sleep that same night. The duration and quality of mothers' sleep was associated with both fathers' and children's sleep that night, whereas fathers' sleep was positively associated with only mothers' sleep. Findings highlight the importance of examining sleep within a family context.